The Effect of Dhyana Education on Knowledge in Lowering Anxiety in Pregnant Women - Rihsan Albahri; Mariana D Lerik; Anderias Umbu Roga; Krispinus Nuban (Ridwan Institute, 2021)
Anxiety during pregnancy almost occurs in all pregnant women in each trimester of pregnancy especially in Primigravida mothers. Anxiety during pregnancy is caused both physically and psychologically. One of the anxiety lowering therapies is Dhyana meditation or Mind concentration. By practicing meditation or concentration of thought get used to being happy at all times, in all even difficult situations, it will gradually free the dir from posikological problems such as anxiety, disappointment and stress. Purpose: this study is to analyze the influence of Dhyana Education on Knowledge in Lowering anxiety in pregnant women. This study uses quasi experiment method and one group pretest-posttest approach. The samples in this study were taken in total sampling as many as 49 pregnant women. Method: Research tool using Dhyana Education questionnaire in lowering anxiety in pregnant women, statistics test using sample paired T-Test. Result: this study shows there is an educational influence of Meditation on knowledge in lowering anxiety in pregnant women primigravida value p= 0.000 (p-value<0.05). Conclusion: Dhyana education affects knowledge in lowering anxiety during pregnancy.